Association of Blood Pressure at Successful Recanalization and Parenchymal Hemorrhage After Mechanical Thrombectomy With General Anesthesia - Cheng, Hui; Xu, Chao; Jin, Xing; Chen, Yigang; Zheng, Xu; Shi, Feina; He, Xudong; Hao, Yonggang; Jiang, Yun; Zhang, Jinhua; Chen, Zhicai (Frontiers in Neurology, 2020)
Background: This study aims to investigate the association between blood pressure (BP) at the time of recanalization and hemorrhagic transformation in large vessel occlusion (LVO) patients following mechanical thrombectomy (MT) with general anesthesia. Methods: We retrospectively reviewed our data base for patients with acute ischemic stroke acute ischemic stroke (AIS) who received MT between January 2018 and December 2019. The BP at two adjacent time points immediately after successful recanalization was recorded for subsequent calculation of mean BP (BPmean), maximum BP (BPmax), minimum BP (BPmin), range of BP (BPrange), and standard deviation of SP (BPSD). Hemorrhagic transformation was identified on 24-h computerized tomography images according to the European Cooperative Acute Stroke Study (ECASS) III trial. We used binary logistic regression analysis to investigate the association of BP parameters and the incidence of parenchymal hemorrhage (PH) and PH-2. Results: A total of 124 patients with anterior circulation LVO were finally included for analyses. After controlling for intravenous thrombolysis, procedure duration of mechanical thrombectomy, baseline National institutes of Health Stroke Scale (NIHSS), baseline ASPECTS, and number of device passes, the results showed that every increment of 10 mmHg in SBPrange (OR 1.559; 95% CI 1.027–2.365; P = 0.037) and SBPSD (OR 1.998; 95% CI 1.017–3.925; P = 0.045) were independently associated with PH. After adjustment for intravenous thrombolysis, procedure duration of mechanical thrombectomy, baseline NIHSS, the results showed that every increment of 10 mmHg in SBPmean (OR 1.973; 95% CI 1.190–3.271; P = 0.008), SBPmax (OR 1.838; 95% CI 1.199 to 2.815; P = 0.005), SBPrange (OR 1.908; 95% CI 1.161–3.136; P = 0.011) and SBPSD (OR 2.573; 95% CI 1.170–5.675; P = 0.019) were independently associated with PH-2. Conclusion: Patients with higher systolic BP and variability at the time of successful recanalization were more likely to have PH-2 in LVO patients following MT with general anesthesia.